2010
DOI: 10.1016/j.jare.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan coating on the characteristics of DPPC liposomes

Abstract: Because it is both biocompatible and biodegradable, chitosan has been used to provide a protective capsule in new drug formulations. The present work reports on investigations into some of the physicochemical properties of chitosan-coated liposomes, including drug release rate, transmission electron microscopy (TEM), zeta potential and turbidity measurement. It was found that chitosan increases liposome stability during drug release. The coating of DPPC liposomes with a chitosan layer was confirmed by electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 44 publications
2
44
0
1
Order By: Relevance
“…The zeta potential (f) of particles was stable due to the repulsion between vesicles by the increase of the surface electrical charge (Mady and Darwish, 2010). In the zeta potential analysis, liposomes positively or negatively charged showed values higher than 30 mV (module).…”
Section: Discussionmentioning
confidence: 99%
“…The zeta potential (f) of particles was stable due to the repulsion between vesicles by the increase of the surface electrical charge (Mady and Darwish, 2010). In the zeta potential analysis, liposomes positively or negatively charged showed values higher than 30 mV (module).…”
Section: Discussionmentioning
confidence: 99%
“…The Dv 50 obtained with ALs in the conventional device was very close to that obtained with the VP3 device. However, a significant increase in Dv 50 and Dv 4,3 was observed for HTCC-ALs from the conventional device, showing droplets more than twice as large (Dv 50 of 40.41±2.78 and 95.36±9.57 µm with ALs and HTCC-ALs, respectively). The potential viscosity afforded by HTCC could be responsible for this evolution, as has been already observed in another study.…”
mentioning
confidence: 90%
“…The nasal administration of peptide with such formulation strategies has already shown interesting properties (also with other administration routes). 49,50 The HTCC-concentration range used after dilution in the AL suspensions for the coating was fixed between 1 mg/mL and 5 mg/mL. 51 Higher HTCC concentrations (.1 mg/mL) did not provide satisfactory results with a PDI larger than 0.198 (data not shown).…”
Section: Htcc-coated Liposomesmentioning
confidence: 99%
“…Chitosan-coated liposomes (so-called chitosomes) were previously prepared by several authors and their effective formation was confirmed using several techniques such as SEM and TEM (11,14,(41)(42)(43).…”
Section: Preparation and Characterizationmentioning
confidence: 99%